Pendidikan Kesehatan tentang Preeklampsia dengan Media Leaflet untuk Meningkatkan Pengetahuan Ibu Hamil - Jujuk Endarwati Eka Wardani; Sulastri Sulastri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of health education about preeclampsia with leaflet media and whether there is an increase in knowledge of pregnant women in the working area of the Parang Health Center. The research method used is quantitative research with a pre-experimental design. The results showed that the average pre-test was 11.6, and the post-test was 17.1. The results of the statistical test showed that there was a significant difference between the pre-test and post-test of knowledge of pregnant women. There is an increase in knowledge after health education about preeclampsia. In conclusion, health education about preeclampsia influences leaflets media in the working area of the Parang Health Center. Keywords: Leaflets, Health Education, Knowledge, Preeclampsia